Executive Politics in Times of Crisis
X, 300 p.
Keywords: Executive Politics in Times of Crisis brings together leading international scholars to consider key trends and challenges that have defined executive politics over the past decade. It showcases key debates in executive politics and contributes to an understanding of the 'executive factor' in political life.